2011
DOI: 10.1111/j.1465-7295.2011.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Information, Institutions, and Banking Sector Development in West Africa

Abstract: Using a new panel dataset for banks in eight West African countries, we explore the factors that exacerbate or alleviate excess liquidity, and the factors that promote or retard the rate of growth of banks" assets. Loan default rates in the region are high, and variations in the rate impact on liquidity and asset growth. However, the size of this effect is very sensitive to bank age. Some types of improvement in the quality of governance reduce excess liquidity and promote asset growth. However, the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 19 publications
(18 reference statements)
3
38
0
Order By: Relevance
“…These findings, which are consistent with the insights of Honohan and Beck (2007), Andrianova et al (2010) and Demetriades and Fielding (2010), highlight the dysfunctional nature of African credit markets. Banking systems could be growing reflecting increased demand for financial services, while vital firm and household credit remains scarce.…”
Section: Summary and Policy Implicationssupporting
confidence: 81%
“…These findings, which are consistent with the insights of Honohan and Beck (2007), Andrianova et al (2010) and Demetriades and Fielding (2010), highlight the dysfunctional nature of African credit markets. Banking systems could be growing reflecting increased demand for financial services, while vital firm and household credit remains scarce.…”
Section: Summary and Policy Implicationssupporting
confidence: 81%
“…Banking conducts in Africa are also significantly different from popular norms in the literature. For example, the legal structure, institutions and financial policies are emerging and unstable (Demetriades & Fielding 2012). Investor protection is generally weak due to weak judicial system and poor enforcement of rules.…”
Section: The Ecowas Banking Environmentmentioning
confidence: 99%
“…Corruption is systemic which heightens banks risk profile (Habib & Zurawicki, 2002). Low financial intermediation and uncertain banking conducts are likely indicators of the high operating risks that banks in this context face which partly explain why banks in Africa have the highest net interest margin compared to banks in other regions of the world (Ahokpossi, 2013;Demetriades & Fielding, 2012;Flamini et al, 2009). …”
Section: The Ecowas Banking Environmentmentioning
confidence: 99%
“…Lastly, the average unemployment rate is around 9.22% with minimum and maximum values of 1.3% and 31.22%. 13 The ratio of impaired loans to gross loans is very high by international standards (see Demetriades and Fielding [35] Table 3 presents the pair-wise correlations matrix of the dependent variable with banks-specific and country-specific variables. The correlation matrix has shown that financial fragility and all explanatory variables are statistically significant at the 5% level, except the bank's efficiency.…”
Section: Resultsmentioning
confidence: 99%